Dual Identities, Single Struggle: A Comparative Analysis of Racial Passing in The Human Stain and Incidents in the Life of a Slave Girl - Sheenam (Integrated Journal for Research in Arts and Humanities, 2024)
This paper undertakes a comparative examination, delving into the portrayal of racial passing in Harriet Jacobs’ Incidents in the Life of a Slave Girl and Philip Roth’s The Human Stain. The study delves into the utilization of racial passing as a mechanism for survival and resistance amongst enslaved individuals during the American antebellum era. The study thoroughly investigates the psychological ramifications of racial passing, the intricate interplay between race and gender, identity crises and trauma endured by characters as a consequence of crossing the colour line. Jacobs’ seminal work offers a firsthand account of the experiences of an enslaved woman navigating the perils of passing to secure her freedom, while Roth's novel delves into the consequences of racial passing in a contemporary American context. Employing interdisciplinary methodology, the analysis draws from literary critique, psychological inquiry, and critical race theory to juxtapose these two works. This study not only enhances the understanding of agency within the context of racial oppression but also highlights the enduring relevance of passing as a theme, exploring the implications for race, individual agency, social dynamics and the construction of identity and acts of resistance within both literary narratives and broader societal contexts.